Matematyka

Autorzy:Karolina Wej, Wojciech Babiański, Ewa Szmytkiewicz, Jerzy Janowicz

Wydawnictwo:Nowa Era

Rok wydania:2016

Wykonaj mnożenie. Jeżeli otrzymasz wyrazy podobne 4.22 gwiazdek na podstawie 9 opinii
  1. Gimnazjum
  2. 2 Klasa
  3. Matematyka

Wykonaj mnożenie. Jeżeli otrzymasz wyrazy podobne

2
 Zadanie

`a) \ \ (x-1)(x^2+x-2)=x*x^2+x*x+x*(-2)-1*x^2-1*x-1*(-2)=`

`=x^3+ul(x^2)-ulul(2x)-ul(x^2)-ululx+2=` `x^3-3x+2` 

`b) \ \ (x+3)(2x^2-x+3)=x*2x^2+x*(-x)+x*3+3*2x^2+3*(-x)+3*3=` 

`=2x^3-ul(x^2)+ulul(3x)+ul(6x^2)-ulul(3x)+9=2x^3+5x^2+9` 

`c) \ \ (x+y-4)(x-y)=(x-y)(x+y-4)=x*x+x*y+x*(-4)-y*x-y*y-y*(-4)=` 

`=x^2+ul(xy)-4x-ul(xy)-y^2+4y=x^2-y^2-4x+4y` 

`d) \ \ (2x-y+6)(x+3y)=(x+3y)(2x-y+6)=x*2x+x*(-y)+x*6+3y*2x+3y*(-y)+3y*6=` 

`=2x^2-ul(xy)+6x+ul(6xy)-3y^2+18y=5xy+2x^2+6x-3y^2+18y` 

`e) \ \ (x-y+2)(x+y-3)=x*x+x*y+x*(-3)-y*x-y*y-y*(-3)+2*x+2*y+2*(-3)=` 

`x^2+ul(xy)-ul(ul(3x))-ul(xy)-y^2+ululul(3y)+ul(ul(2x))+ululul(2y)-6=x^2-x+5y-y^2-6` 

`f) \ \ (x^2+x+1)(x^2-x+1)=x^2*x^2+x^2*(-x)+x^2*1+x*x^2+x*(-x)+x*1+1*x^2+1*(-x)+1*1=` 

`x^4-ululx^3+ul(x^2)+ululx^3-ul(x^2)+ulululx+ul(x^2)-ulululx+1=x^4+x^2+1`